Molecular characterization of vancomycin-resistant Enterococcus faecium isolates from two German hospitals - Nürnberger, Laura; Schmidt, Dirk; Szumlanski, Tobias; Kirchhoff, Lisa; Ross, Birgit; Steinmann, Jörg; Rath, Peter-Michael (German Medical Science GMS Publishing House, 2021)
Introduction: Vancomycin-resistant accounts for around 10-23% of nosocomial enterococcal infections and constitutes a relevant therapeutic problem due to its limited susceptibility to antibiotics. The resistance towards glycopeptide antibiotics is mediated by the so-called van genes. Currently, the most common resistance type in Germany is the -type. Little data are available on the molecular epidemiology in Germany. Therefore, an epidemiological typing of isolates with vanB-type resistance from two German hospitals in Essen and Nuremberg was performed. Two outbreaks and 104 sporadic cases were investigated. Methods: All 128 isolates with -type resistance were collected between 2011-2012 and 2017-2018. They were characterized using multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). Results: ST 117 was the most common sequence type (ST) in both hospitals, especially since 2017. PFGE divided the isolates of this study into 68 PFGE types and showed a broad genetic diversity. Two epidemiologically assumed in-hospital outbreaks were genetically confirmed. Apart from that, in-hospital transmissions were rare events. Conclusion: The results obtained by MLST confirmed the previously described allocation of STs in Germany. PFGE showed a broad genetic diversity of VRE between the two hospitals and also within each hospital. In-hospital transmissions were rare, but outbreaks did occur. Our data supports the strategy to screen and isolate patients in transmission events in order to detect monoclonality indicating a common source or hygiene mismanagement.